Responsabilidad estatal en la vulneración de los derechos laborales a consecuencia del COVID 19 - Vera Miño, Emy Elizabeth (2022)
The theme "State Responsibility in the violation of Labor Rights as a result of COVID19", presented the general objective to theoretically examine the responsibility of the Ecuadorian State regarding the labor decisions adopted in the Organic Law of Humanitarian Support and the violation of the rights jobs within it. In this sense, the investigation was justified in the theoretical part with the different conceptualizations and the antecedents, taken from other investigations. It is important to highlight that the qualitative approach was considered in the methodology, carried out through interviews, using online platforms, which allowed supporting the questions raised in the research. The sample was four lawyers from the Guayaquil canton. In the results, it was obtained that the legal basis establishes that the State has to take responsibility for the acts that are part of the established norm, especially when it is to the detriment of citizens. Another result observed that the reduction of the working day and salary decrease without being stipulated in the law, violated labor rights. In the proposal for the reform of the Law, it is justified in accordance with the regulations of the CRE, Art. 102, which mentions that Ecuadorians can present projects, through the mechanisms provided for in the Constitution and the law. In conclusion, in the LOAH there are certain articles that harm workers, especially when it involves "negotiating" the salary part and the work schedule, which goes against their rights that are established in the Labor Code.